Optimizing the Personnel Position Monitoring System Using the Global Positioning System in Hostage Release - Irmanto, Dodo; Sujito, Sujito; Aripriharta, Aripriharta; Widiatmoko, Dekki; Kasiyanto, Kasiyanto; Omar, Saodah (Universitas Nusantara PGRI Kediri, 2024)
In the contemporary era of globalization, maintaining public order depends on strong security measures. Addressing security challenges, particularly in hostage release scenarios, requires rapid and appropriate responses, highlighting the need for efficient personnel deployment. This research proposes an advanced solution using a GPS Tracking System which uses a sequential method by utilizing digital photos from GPS satellites to monitor the movement of individuals and objects. Specifically applied to the Sandra rescue mission, our research uses the NodeMCU ESP8266 component, which integrates GPS and Wi-Fi functions while considering wind direction. Tests performed demonstrated an impressive success rate of 98.6%, demonstrating the effectiveness of our real-time personnel positioning approach.